My adult son, my adult daughter – reflections of mothers of children with profound intellectual disabilities - Aksamit, Diana; Marcinkowska, Barbara (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Diana Aksamit, Barbara Marcinkowska, My adult son, my adult daughter – reflec-tions of mothers of children with profound intellectual disabilities. Interdisciplinary Contexts of Special Pedagogy, no. 26, Poznań 2019. Pp. 255–269. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.26.12 Everyone has the right to participate in society, regardless of his or her current personal situation, level of psychosocial functioning or experience. No reason can justify marginalisation or exclusion of people from social life at any stage of their lives. The aim of the article is an attempt to characterise the adulthood of people with profound intellectual disabilities on the basis of subjective assessment of their mothers. The methodology applied was that of a qualitative research, where the main research technique was narrative interviews. The results of the research demonstrate that adulthood is the stage of life when people with profound intellectual disabilities and their caregivers require special support in mental, spiritual, social, societal and educational dimensions.